First order normalization in the generalized photo gravitational non-planar restricted three body problems - Sinha, Nirbhay Kumar (International Journal of Advanced Astronomy, 2015)
In this paper, we normalised the second-order part of the Hamiltonian of the problem. The problem is generalised in the sense that fewer massive primary is supposed to be an oblate spheroid. By photogravitational we mean that both primaries are radiating. With the help of Mathematica, H2 is normalised to H2 = a1b1w1 + a2b2w2. The resulting motion is composed of elliptic motion with a short period (2p/w1), completed by an oscillation along the z-axis with a short period (2p/w2).